Структуралізм в образотворчому мистецтві ХХ століття - Марчук, Н. (Інститут народознавства НАН України, 2007)
Structuralism is considered as the characteristic phenomenon in the fine art of the XX-th century. A lot of artists have developed the idea of structuralism in their creation (Pieter Mondrian, Victor Vazareli, Maurits Escher and others). Using certain principles and methods abstracting they imparted to works of art new forms of artistic expressiveness. Some of their graphic and composition principles of structuralisation of representation became fundamental. These principles had their continuation and support in the historical process of the fine art development in graphic and Web. design.